Integrated System of Reverse Osmosis and Forward Pressure-Assisted Osmosis from ZrO2 Base Polymer Membranes for Desalination Technology - Saleh O. Alaswad; Heba Abdallah; Eman S. Mansor (Technologies, 2024)
In this work, reverse osmosis and forward osmosis membranes were prepared using base cellulosic polymers with ZrO2. The prepared membranes were rolled on the spiral-wound configuration module. The modules were tested on a pilot unit to investigate the efficiency of the RO membrane and the hydraulic pressure effect on both sides of the FO membranes. The RO membrane provided a rejection of 99% for the seawater desalination, and the brine was used as a draw solution for the FO system. First, seawater was used as a draw solution to indicate the best hydraulic pressure, where the best one was 3 bar for the draw solution side, and 2 bar for the feed side, where the water flux reached 48.89 L/m2·h (LMH) with a dilution percentage of 80% and a low salt reverse flux of 0.128 g/m2·h (gMH) after 5 h of operation time. The integrated system of RO and forward-assisted osmosis (PAO) was investigated using river water as a feed and RO brine as a draw solute, where the results of PAO indicate a high-water flux of 68.6 LMH with a dilution of 93.2% and a salt reverse flux of 0.18 gMH. Therefore, using PAO improves the performance of the system.